2023
DOI: 10.1007/s00482-022-00686-2
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Wirksamkeit der aurikulären Vagusnervstimulation in der Behandlung chronischer und akuter Schmerzen

Abstract: Zusammenfassung Hintergrund Aktuelle Leitlinien empfehlen für die Behandlung chronischer Schmerzen einen personalisierten, multimodalen und interdisziplinären Ansatz. Bereits in der akuten Behandlung postoperativer Schmerzen kann es sinnvoll sein, Risikofaktoren für die Chronifizierung zu minimieren. Die aurikuläre Vagusnervstimulation (aVNS) könnte eine effektive nichtmedikamentöse Therapie zur Behandlung von Schmerzen darstellen. Ziel der Arbeit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…Similar autonomic modulatory effects have been observed in clinical trials of acupuncture for migraine and lower back pain and are consistent with the results of a recent meta-analysis (Hamvas et al, 2023). Auricular vagus nerve stimulation is an effective therapy for both chronic and acute pain (Likar et al, 2023). Studies have demonstrated that auricular acupuncture can also increase HRV and vagal activity during pain relief (Butt et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
“…Similar autonomic modulatory effects have been observed in clinical trials of acupuncture for migraine and lower back pain and are consistent with the results of a recent meta-analysis (Hamvas et al, 2023). Auricular vagus nerve stimulation is an effective therapy for both chronic and acute pain (Likar et al, 2023). Studies have demonstrated that auricular acupuncture can also increase HRV and vagal activity during pain relief (Butt et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
“…The ineffectiveness of lateralization is believed to be attributed to the fact that the analgesic impact of vagal stimulation was a result of central inhibition rather than peripheral nociceptive processes [14]. In their study examining the impact of vagal stimulation on acute and chronic pain, Likar et al [23] determined that it has the potential to be a remarkable and supplementary alternative to medication for managing chronic and acute postoperative pain.…”
Section: Discussionmentioning
confidence: 99%